2010
DOI: 10.1016/j.icarus.2009.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of (2) Pallas

Abstract: a b s t r a c tGround-based high angular-resolution images of asteroid (2) Pallas at near-infrared wavelengths have been used to determine its physical properties (shape, dimensions, spatial orientation and albedo distribution).We acquired and analyzed adaptive optics (AO) J/H/K-band observations from Keck II and the Very Large Telescope taken during four Pallas oppositions between 2003 and 2007, with spatial resolution spanning 32-88 km (image scales 13-20 km/pixel). We improve our determination of the size, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 50 publications
4
69
0
Order By: Relevance
“…A complete description of the method can be found elsewhere , as well as an example of its application on (2) Pallas (Carry et al 2010).…”
Section: The Koala Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A complete description of the method can be found elsewhere , as well as an example of its application on (2) Pallas (Carry et al 2010).…”
Section: The Koala Methodsmentioning
confidence: 99%
“…The optical lightcurves bring indirect constraints on the shape of Lutetia, provided the albedo is homogeneous over its surface. Indeed, lightcurves are influenced by a combination of the asteroid shape 4 and albedo variation (see the discussion by Carry et al 2010, regarding the effect of albedo features on the shape reconstruction).…”
Section: The Koala Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent recovery of the Almahata Sitta meteorite, originating from the impact of asteroid 2008 TC 3 on Earth in October 2008, indeed indicated that B-type could be associated with unusual Ureilite achondrites (Jenniskens et al 2009). Based on a comparison of the densities of (1) Ceres and (2) Pallas (used as archetypes for the definition of C and B taxonomic classes), Carry et al (2010a) had suggested that B-types were less hydrated than C-types; a hypothesis supported by the lack of signature of organic or icy material in their spectra (Jones et al 1990). …”
Section: C-complex and Sub-groupsmentioning
confidence: 99%
“…Based on previously determined sizes of Lutetia, with diameters ranging from 96 km from IRAS (Tedesco et al 2002(Tedesco et al , 2004 to 116 km from radar (Magri et al 1999(Magri et al , 2007, Lutetia should have presented an apparent diameter of 0.10 , slightly more than twice the diffraction limit of the Keck Observatory 10 m telescope at infrared wavelengths (1−2 μm). Continuing our campaign (Conrad et al 2007;Drummond et al 2009;Carry et al 2010a) to study asteroids resolved with the world's large telescopes equipped with adaptive optics (AO), we have acquired more than 300 images of Lutetia, most from the 2008-09 season. An exceptionally good set of 81 images was obtained on 2008 December 2 with the Keck II telescope, which, despite the high sub-Earth latitude, yields a full triaxial ellipsoid solution from the changing apparent ellipses projected onto the plane of the sky by the asteroid.…”
Section: Introductionmentioning
confidence: 99%